The Okun Misery Index in the European Union Countries from 2000 to 2009 - Grabia, Tomasz (Comparative Economic Research. Central and Eastern Europe, 2012)
The aim of the article is to present alternative measures of the economic system’s efficiency, taking into consideration, in particular, the values of the so called Okun misery index being the sum of inflation and unemployment rates. The study is composed of four main parts and a summary. The first part, introduction, discusses various measures of the economic system’s efficiency that are used in practice. Part two emphasises that the GDP per capita according to purchasing power parity still remains the most popular among those measures. Further, it presents the ranking of the European Union countries taking that measure into account, the research period being 1999- 2009. Part three points out that it is also the level of poverty (misery) that determines the economic system’s efficiency. That level can be measured by means of various indicators, among others, the so called HPI-2 index calculated by the UN. It will be the Okun misery index, however, computed as the sum of inflation and unemployment rates that will be presented as an alternative being of interest from the macroeconomic point of view. The ranking of the European Union member states according to that measure in the 2000-2004 and 2005- 2009 periods will be provided in part four. The article will end in a summary containing synthetic conclusions drawn from earlier observations.